Communication failures contributing to patient injury in anaesthesia malpractice claims☆. (September 2021) - Douglas, Rachel N.; Stephens, Linda S.; Posner, Karen L.; Davies, Joanna M.; Mincer, Shawn L.; Burden, Amanda R.; Domino, Karen B.
Abstract: Background: Communication amongst team members is critical to providing safe, effective medical care. We investigated the role of communication failures in patient injury using the Anesthesia Closed Claims Project database. Methods: Claims associated with surgical/procedural and obstetric anaesthesia and postoperative pain management for adverse events from 2004 or later were included. Communication was defined as transfer of information between two or more parties. Failure was defined as communication that was incomplete, inaccurate, absent, or not timely. We classified root causes of failures as content, audience, purpose, or occasion with inter-rater reliability assessed by kappa. Claims with communication failures contributing to injury (injury-related communication failures; n =389) were compared with claims without any communication failures ( n =521) using Fisher's exact test, t -test, or Mann–Whitney U -tests. Results: At least one communication failure contributing to patient injury occurred in 43% ( n =389) out of 910 claims (κ=0.885). Patients in claims with injury-related communication failures were similar to patients in claims without failures, except that failures were more common in outpatient settings (34% vs 26%; P =0.004). Fifty-two claims had multiple communication failures for a total of 446 injury-related failures, and 47% of failures occurred during surgery, 28% preoperatively, and 23% postoperatively. Content failures (insufficient, inaccurate, or no information transmitted) accounted for 60% of the 446 communication failures. Conclusions: Communication failure contributed to patient injury in 43% of anaesthesia malpractice claims. Patient/case characteristics in claims with communication failures were similar to those without failures, except that failures were more common in outpatient settings.